Social vulnerability index associated with higher COVID-19 seroprevalence in Nigeria - Natalia Blanco; Olanrewaju Lawal; Jibreel Jumare; Christina Riley; James Onyemata; Thomas Kono; Anna Winters; Chenfeng Xiong; Alash’le Abimiku; Manhattan Charurat; Kristen A. Stafford; for The INFORM Africa Research Study Group (Global Health Action)
Social vulnerability has been shown to be a strong predictor of disparities in health outcomes. A common approach to estimating social vulnerability is using a composite index, such as the social vulnerability index (SVI), which combines multiple factors corresponding to key social determinants of health. Lawal and Osayomi created an SVI to explore key social determinants of health-related COVID-19 infection among the Nigerian population. This study explored the association of COVID-19 SVI with COVID-19 seroprevalence using a large household survey in Nigeria. Weighted COVID-19 seroprevalence estimates at the Local Government Areas (LGA) were estimated and merged with the Lawal and Osayomi SVI, also at the LGA-level. Linear regression models were constructed to evaluate the relationship between the SVI and COVID-19 seroprevalence. The effect of SVI was evaluated both as a continuous variable and categorized into quintiles to evaluate dose–response effects. Our results confirmed a positive relationship between social vulnerability and COVID-19 infection in four states and the Federal Capital Territory in Nigeria. Compared to class 1 (the least vulnerable group), COVID-19 seroprevalence was, on average, 9.21% and 6.42% higher in classes 4 and 5 LGAs, respectively, after adjustment by phase of the survey. The effect was particularly strong farther into the pandemic (June 2021), when COVID-19 mitigation measures were relaxed. In conclusion, SVI can potentially be a useful tool to effectively prioritize communities for resource allocation as part of emergency response and preparedness in Africa.